The ConsuMEER study: a randomised trial towards the effectiveness of protein-rich ready-made meals and protein-rich dairy products in increasing protein intake of community-dwelling older adults after switching from self-prepared meals towards ready-made meals. (2019) - Borkent, Jos W.; Beelen, Janne; Linschooten, Joost O.; Roodenburg, Annet J. C.; de van der Schueren, Marian A. E.
Abstract: The risk of undernutrition in older community-dwelling adults increases when they are no longer able to shop or cook themselves. Home-delivered products could then possibly prevent them from becoming undernourished. This single-blind randomised trial tested the effectiveness of home-delivered protein-rich ready-made meals and dairy products in reaching the recommended intake of 1·2 g protein/kg body weight (BW) per d and ≥25 g of protein per meal. Community-dwelling older adults ( n 98; mean age 80·4 (sd 6·8) years) switched from self-prepared to home-delivered hot meals and dairy products for 28 d. The intervention group received ready-made meals and dairy products high in protein; the control group received products lower in protein. Dietary intake was measured at baseline, after 2 weeks (T1), and after 4 weeks (T2). Multilevel analyses (providing one combined outcome for T1 and T2) and logistic regressions were performed. Average baseline protein intake was 1·09 (se 0·05) g protein/kg BW per d in the intervention group and 0·99 (se 0·05) g protein/kg BW per d in the control group. During the trial, protein intake of the intervention group was 1·12 (se 0·05) g protein/kg BW per d compared with 0·87 (se 0·03) g protein/kg BW per d in the control group (between-group differences P < 0·05). More participants of the intervention group reached the threshold of ≥25 g protein at dinner compared with the control group (intervention T1: 84·8 %, T2: 88·4 % v. control T1: 42·9 %, T2: 40·5 %; P < 0·05), but not at breakfast and lunch. Our findings suggest that switching from self-prepared meals to ready-made meals carries the risk of a decreasing protein intake, unless extra attention is given to protein-rich choices.